MOTIVASI DALAM ORGANISASI USAHA - Firmansyah (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2017)
One of important things that should be a concern in business activities is the motivation of actors involved in business activities, various theories about motivation such as content theory and process theory, Hierarchy of Need Theory (A. Maslow), Theory Three Social Motivation (D. McClelland), The Two-Factor Theory (Frederick Herzberg), these theories provide a brief explanation of how individual behaviors in their daily activities are viewed from various aspects that underlie the emergence of such behaviors, causative factors, motivations and how to keep it. The dynamics of the fast-changing business world of course requires high spirits for the perpetrators this is of course a special requirement, especially for business owners and managers in the business environment so that people they lead can perform activities in accordance with the duties and responsibilities to obtain results maximum in order to spur productivity to earn profit. So that the sustainability of the business can be maintained because the interested parties already have the knowledge and various strategies to keep the motivation himselfand the employees who become under him.